Pch Genes Control Biofilm and Cell Adhesion in a Clinical Serotype O157:H7 Isolate - Andreozzi, Elisa; Gunther, Nereus W.; Reichenberger, Erin R.; Rotundo, Luca; Cottrell, Bryan J.; Nuñez, Alberto; Uhlich, Gaylen A. (Frontiers in Microbiology, 2018)
In a previous study, induction of the Escherichia coli serotype O157:H7 SOS response decreased csgD expression in the clinical isolate PA20 at 30°C but strongly induced genes in the horizontally-transferred-DNA regions (HTR), including many known virulence regulators. To determine the role of HTR regulators in the control of csgD and curli, specific regulators were plasmid-expressed in wild-type and mutant strains of PA20 and its strong biofilm-forming derivative, 20R2R. The O157:H7 group 3 perC homologue, pchE, strongly repressed csgD and CsgD-dependent phenotypes such as biofilm formation and Congo red dye affinity in a ler-independent manner at 30°C. At 37°C under non-SOS inducing conditions, curli, rather than espA, contributed to host cell adhesion and pchE was capable of minimizing the curli-dependent cell adherence, providing a host-adapting adhesion control mechanism. Expression of pchE was also repressed during SOS response induction at 37°C, providing a mechanism by which curli expression might complement the group1 pch initiated espA-dependent intimate adhesion.